Atravessamentos da Amazônia : sobre o corpo e a subjetividade na produção do real - Andrade, Aline Moschen de (2017)
The present text is a continuation of the Amazon river population research done in 2012 by me. In this, we revisit the diaries, audio recordings and photographs used as ethnographic tools during the field research to do a new elaboration on events regarding ribeirinha's subjectivity and her naratives. The proposal is to think the real as invention, the composition of collectives bodies and the composition of researcher-body. The Bergson's conception about the real is the main theoretical reference, a notion of production that guides the results of this work.